2023
DOI: 10.1039/d3cy01013a
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of spinel CoFe2O4 as an electrocatalyst for the oxygen evolution reaction

Hongxin Wang,
Qiming Hu,
Jiangyuan Qiu
et al.

Abstract: To satisfy the energy demand of modern society, seeking sustainable, clean and efficient energy production is claimed to be significant. Electrolytic water technology is an efficient and sustainable way to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 103 publications
1
3
0
Order By: Relevance
“…Original 18 O-isotopic labeling experiments showed that the OER on SrCoO 3−δ performed via both AEM and LOM pathways . Our group also confirmed that the OER reaction was driven by both mechanisms, which was verified by experimental calculations, in situ Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). , However, during the development of OER electrocatalysts, the generation of HOO* in the AEM and the step of deprotonation in the LOM are considered bottlenecks …”
Section: Oer Mechanismssupporting
confidence: 72%
See 3 more Smart Citations
“…Original 18 O-isotopic labeling experiments showed that the OER on SrCoO 3−δ performed via both AEM and LOM pathways . Our group also confirmed that the OER reaction was driven by both mechanisms, which was verified by experimental calculations, in situ Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). , However, during the development of OER electrocatalysts, the generation of HOO* in the AEM and the step of deprotonation in the LOM are considered bottlenecks …”
Section: Oer Mechanismssupporting
confidence: 72%
“…43,44 However, during the development of OER electrocatalysts, the generation of HOO* in the AEM and the step of deprotonation in the LOM are considered bottlenecks. 45 2.4. COM and OPM.…”
Section: Oer Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations